’He said he was going to kill me’: Case Studies of Attempted Intimate Femicide in São Paulo, Brazil - Evans, Dabney P.; Williams, Nancy S. DeSousa; Wilkins, Jasmine D.; Chiang, Ellen D.; Manders, Olivia C.; Vertamatti, Maria A.F. (Journal of Comparative Social Work, 2018)
This article uses a case study design to explore attempted intimate femicide in metropolitan São Paulo, Brazil. We conducted 30 in-depth interviews with adult women on community and personal relationship experiences, health-care services, and national legislation about violence against women. Through a thorough transcript review, we identified two participants, Maria* and Raquel*, whose intimate partners attempted to kill them. We used a modified grounded theory approach to code the entire sample, and further analysed these transcripts to identify missed opportunities for intervention in both the prevention of- and responses to intimate partner violence (IPV), and the antecedents of attempted intimate femicide. Both women had normalized experiences of violence, and experienced psychological abuse prior to the attempted intimate femicide. Social and familial networks were sources of shame for Raquel and support for Maria. Neither woman expressed confidence in law enforcement’s ability to protect women and girls from IPV. These cases illustrate the need for multi-tiered interventions to prevent femicide in Brazil, which boasts one of the highest global female homicide rates. Although anti-femicide laws exist, better mechanisms are needed to integrate health, legal and social services for IPV and femicide prevention. In addition, community- and interpersonal- level interventions that counteract the Brazilian ‘culture of violence’ and machismo may provide support for at-risk women and girls. *pseudonyms have been used to protect the identity of the participants